Politics and Power in Haiti - Quinn, K.; Sutton, P.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Examining the political legacies of the Duvalier period and after, and revisiting the work of the late David Nicholls, Politics and Power in Haiti provides some of the keys to understanding the turbulent world of Haitian politics and the persistent challenges at home and from abroad which have distorted development.
Keywords: America—History.; Latin America—Politics and government; Ethnology—Latin America; International relations; Political science; Economic development; History of the Americas; Latin American Politics; Latin American Culture; International Relations; Political Science; Development Studies